A systematic review and meta‐analysis of cell‐based interventions in experimental diabetic kidney disease. (9th June 2021) - Hickson, LaTonya J.; Abedalqader, Tala; Ben‐Bernard, Gift; Mondy, Jayla M.; Bian, Xiaohui; Conley, Sabena M.; Zhu, Xiangyang; Herrmann, Sandra M.; Kukla, Aleksandra; Lorenz, Elizabeth C.; Kim, Seo Rin; Thorsteinsdottir, Bjorg; et al.
Abstract: Regenerative, cell‐based therapy is a promising treatment option for diabetic kidney disease (DKD), which has no cure. To prepare for clinical translation, this systematic review and meta‐analysis summarized the effect of cell‐based interventions in DKD animal models and treatment‐related factors modifying outcomes. Electronic databases were searched for original investigations applying cell‐based therapy in diabetic animals with kidney endpoints (January 1998‐May 2019). Weighted or standardized mean differences were estimated for kidney outcomes and pooled using random‐effects models. Subgroup analyses tested treatment‐related factor effects for outcomes (creatinine, urea, urine protein, fibrosis, and inflammation). In 40 studies (992 diabetic rodents), therapy included mesenchymal stem/stromal cells (MSC; 61%), umbilical cord/amniotic fluid cells (UC/AF; 15%), non‐MSC (15%), and cell‐derived products (13%). Tissue sources included bone marrow (BM; 65%), UC/AF (15%), adipose (9%), and others (11%). Cell‐based therapy significantly improved kidney function while reducing injury markers (proteinuria, histology, fibrosis, inflammation, apoptosis, epithelial‐mesenchymal‐transition, oxidative stress). Preconditioning, xenotransplantation, and disease‐source approaches were effective. MSC and UC/AF cells had greater effect on kidney function while cell products improved fibrosis. BM and UC/AF tissue sources more effectively improved kidney function and proteinuria vs adipose or other tissues. Cell dose, frequency, and administration route also imparted different benefits. In conclusion, cell‐based interventions in diabetic animals improved kidney function and reduced injury with treatment‐related factors modifying these effects. These findings may aid in development of optimal repair strategies through selective use of cells/products, tissue sources, and dose administrations to allow for successful adaptation of this novel therapeutic in human DKD. Abstract : Cell‐based therapies improve diabetic kidney repair: a systematic review and meta‐analysis.